Intelligence in early adulthood and subsequent hospitalisation and admission rates for the whole range of mental disorders: longitudinal study of 1,049,663 men - Gale, Catharine R. (2010)
BACKGROUND: Lower intelligence is a risk factor for several specific mental disorders, but it is unclear whether it is a risk factor for all mental disorder or whether it is associated with illness severity. We examined the relation between pre-morbid intelligence and risk of hospital admission and total admission rates for the whole range of mental disorders. METHODS: Participants were 1,049,663 Swedish men who took tests of intelligence on conscription into military service and were followed up for hospital admissions for mental disorder for a mean of 22.6 years. International Classification of Diseases diagnoses were recorded at discharge from hospital. RESULTS: Risk of hospital admission for all categories of disorder rose with each point decrease in the nine-point IQ score. For a standard deviation decrease in IQ, age-adjusted hazard ratios (95% CI) were 1.60 (1.55, 1.65) for schizophrenia, 1.49 (1.45, 1.53) for other non-affective psychoses, 1.50 (1.47, 1.51) for mood disorders, 1.51 (1.48, 1.54) for neurotic disorders, 1.60 (1.56, 1.64) for adjustment disorders, 1.75 (1.70, 1.80) for personality disorders, 1.75 (1.73, 1.77) for alcohol-related and 1.85 (1.82, 1.88) for other substance use disorders. Lower intelligence was associated with greater comorbidity. Associations changed little on adjustment for potential confounders. Men with lower intelligence had higher total admission rates, a possible marker of clinical severity. CONCLUSIONS: Lower intelligence is a risk factor for the whole range of mental disorders and for illness severity. Understanding the underlying mechanisms is crucial if we are to find ways to reduce the burden of mental illness.